Optimalisasi Pendapatan Badan Layanan Umum Daerah Kota Bandung Terhadap Retribusi Parkir Perspektif Siyasah Maliyah - Faris Faturohman; Lutfi Fahrul Rizal; Taufiq Alamsyah (LPPM Universitas Ekasakti Padang, 2024)
This research discusses the analysis of siyasah maliyah towards optimizing the income of the Regional Public Service Agency from parking fees. The aim of this research is to determine the mechanism for collecting parking fees based on Bandung City Regional Regulation Number. 3 of 2020 and Bandung City Regulation Number 634 of 2017, as well as to find out the Siyasah Maliyah review of the management of parking fees based on Bandung City Regional Regulation Number. 3 of 2020 and Bandung City Regulation Number 634 of 2017. The method used in this research is a qualitative research method with an empirical juridical approach. Based on the results of this research, collection of parking fees in Bandung City is carried out using two methods, namely manual and using a parking machine. Even though the income from manual collection is higher than using electronic machines, there are still many leakages in field collection. Even though parking rates have been regulated in regional regulations, there are still violations in their determination by parking managers. The implementation of government policies must be in accordance with the principles of Islamic law, especially in safeguarding assets (hifdz mal), and follow the principles of Maliyah siyasah such as justice and maslahah.